AB0228 Cardiovascular risk in ethnic minorities with rheumatoid arthritis. (23rd January 2014) - Kerr, G.; Yazici, Y.; Swearingen, C.; Luo, C.; Espinoza, L.; Sherrer, Y.; Treadwell, E.; Mosley-Williams, A.; Alamino Perez, R.; Bata, Y.; Dowell, S.; Godoy, A.; et al.
Abstract : Background: Cardiovascular (CVD) comorbidity and mortality in rheumatoid arthritis (RA), is well documented. 1 Increased prevalence of the metabolic syndrome, higher disease activity, greater prednisone and less DMARD usage are established contributors. RA patients are less frequently evaluated for CVD risk factors 2 . Yet, ethnic minorities have a greater prevalence of CVD risk factors and events. Objectives: To evaluate the CVD risk scores in ethnic minority RA patients. Methods: Enrolled, consented EMRAC patients were evaluated. Data collected include socio-demographic, RA disease severity and activity-related parameters, tobacco use, prednisone and DMARD/biologic usage, and comorbidities (HTN, DM, lipidemia, CVD event). Additional data included systolic BP, total cholesterol (TC), LDL, HDL. Coronary heart disease (CHD) and non-coronary cardiovascular disease (CVD) 10-year risk SCORES 3 were calculated for ethnic minority subsets, and association with RA disease-related variables and treatments evaluated. CHD and CVD 10 yr-risk scores were sumarrized as continuous and dichotomozied at >5%. Results: 156 EMRAC patients had complete datasets for analysis. The majority were female, 142(91%), of mean age 58.1 (13.6) years, with mean disease duration 8.9 (7.8) years. 70 (45%) were Caucasian, 20 (13%) were African-American, 26 (17%) were Hispanic with 40 (26%) Other. Mean values for lipids were as follows: HDL, 64.9 (17.1) mg/dl, LDL 104(33.5) mg/dl and TC 191(39.0) mg/dl. Mean Systolic BP was 124.4(16.5) mmHg. CVD risk is summarized in Table . Dichotomizing the predicted risk score at 5%, our cohort's fatal CVD risk ranged from 14% (low risk profile) to 20% (high risk profile). However, 25% of the African-Americans had a 5% risk (low and high risk profiles) compared to Caucasians risk which ranged from 9% to 17% (low risk and high risk profile, respectively), but did not reach statistical signficance. Image/graph: Conclusions: EMRAC patients are at risk for fatal CVD events. While the limited sample size precluded statistical significance in ethnic differences, there is the potential for clinical relevance and our findings call for due diligence in minimizing CVD risk factors. References: Meune, C. Arch Cardiovasc Dis. 2010 Desai, S. Arth. Res Ther. 2012 Peters, M. Ann. Rheum Dis, 2010 Disclosure of Interest: G. Kerr Grant/research support from: EMRAC receives unrestricted grant support from Genentech, Pfizer and Bristol Myers Squibb, Y. Yazici: None Declared, C. Swearingen: None Declared, C. Luo: None Declared, L. Espinoza: None Declared, Y. Sherrer: None Declared, E. Treadwell: None Declared, A. Mosley-Williams: None Declared, R. Alamino Perez: None Declared, Y. Bata: None Declared, S. Dowell: None Declared, A. Godoy: None Declared, M. Paul: None Declared